Perceived Sources of Happiness: Things Bhutanese think would make them live a truly happy life. - Wangdi, Karma (Journal of Bhutan Studies)
The Royal Government of Bhutan is constitutionally mandated to promote enabling conditions for people to pursue happiness. Although investigator-determined sources of happiness such as nine domains and 33 indicators of GNH index are being discussed widely among the policymakers and used as planning tools, participant-generated sources of happiness has not been studied in detail, let alone featuring in policy discourse. This study is aimed at answering two questions: a) what are the perceived sources of happiness for Bhutanese, and b) how does the perceived sources of happiness differ among people belonging to different socio-demographic subgroups. Text data collected through nationally representative sample survey involving 8,871 Bhutanese aged 15 years or older using open-ended question was content analysed, classified and coded using inductive category development approach and deductive category application approach. Inter-rater reliability test using Cohen's kappa (Κ) was conducted to ensure reliability of classification and coding process. A total of 18,850 statements of the perceived sources of happiness reported by 7,141 respondents were classified into 18 major categories and 42 sub-categories of sources of happiness. The most frequently cited source of happiness among 18 major categories is 'money and financial security' (19.6%) followed by 'health and wellbeing' (13.5%), 'asset ownership' (11.9%), 'family and family relationships' (11.2%), 'access to facilities and services' (11.1%), 'education, employment and future success of significant others' (8.8%), and 'education, employment and job satisfaction' (7.2%). The remaining 11 categories accounted for about 17 percent of the total responses.